Mapeamento do perfil do egresso de um programa de pós-graduação em otorrinolaringologia - Silva, Maria Jose da [UNIFESP] (2018)
Introduction: To evaluate the profile of alumni of the students of Strictosensu postgraduation programs is fundamental to qualitatively analyze the results obtained by those programs, including graduation of professors and researchers, and also to develop policies to obtain continuous improvements of the programs. Objectives: To evaluate the profile of the alumni of the Otorhinolaryngology postgraduation program of our postgraduation program, and to analyze its impact in their professional development. Methods: We performed a crosssectional study, involving analysis of the data collected from the database of students who graduated our Stricto sensu program (masters, doctors and postdoctoral degrees) from 1979 to 2017. Results: The Otorhinolaryngology postgraduation program of the UNIFESP/EPM has graduated 489 students (63% master, 35% doctorate, and 2% postdoctoral degrees); most of the former students were men (63%). Most of the alumni were M.D.s (83%), while 17% were not. Thirtynine percent of the alumni have published scientific studies extracted from their thesis. Over 65% of the former students are currently working as professors. Discussion: We observed profile changes regarding sex and formation (M.D.s and nonM. D.s) through the years, which may reflect historic tendencies (increase in number of women) and also changes to the national politics directed to the development of the postgraduation programs. The high number of alumni who are currently enrolled as professors also demonstrate that the objectives of our institution are currently being adequately achieved. Conclusion: The program is graduating professors and researchers who work in all regions of the Brazilian territory and also abroad. There was an increase in number of the publication of scientific studies extracted from the thesis in the last two decades, and the quality of those publications are in accordance with the standards set by CAPES in 2016.